High PDL1 mRNA expression predicts better survival of stage pT1 non-muscle-invasive bladder cancer (NMIBC) patients - Breyer, Johannes; Erben, Philipp; Worst, Thomas (Cancer immunology immunotherapy, 2018)
Introduction and objectivesCheckpoint inhibition has emerged as new therapeutic option in muscle-invasive bladder cancer. The objective of the present study was to evaluate the prognostic role of PD1 and PDL1 expression in non-muscle-invasive bladder cancer (NMIBC) and establish an objective measuring method using RNA quantification.Materials and methodsWe retrospectively analyzed clinical data and formalin-fixed paraffin-embedded tissues (FFPE) of patients with stage pT1 NMIBC who underwent transurethral resection of the bladder. mRNA expression of PD1, PDL1 and CD3 was measured by single step RT-qPCR and correlated to clinicopathological parameters, recurrence-free survival (RFS), progression-free survival (PFS) and carcinoma-specific survival (CSS).ResultsWe have analyzed 334 patients with NMIBC at stage pT1 for mRNA analysis. Data from 296 patients (79% male, median age: 72 years) could be used. Spearman correlation revealed significant associations between mRNA expressions of PD1/PDL1 (ρ: 0.6024, p < 0.0001), CD3/PDL1 (ρ: 0.5728, p < 0.0001) and CD3/PD1 (ρ: 0.7005, p < 0.0001). Kaplan-Meier analysis revealed that high PDL1 mRNA expression (≥ 33.83) is a favorable prognostic factor with regard to better RFS (p = 0.0018), PFS (p = 0.021) and CSS (p = 0.012). Multivariate Cox-regression analysis proved PDL1 expression to be an independent prognosticator for RFS [HR 0.48 (0.31-0.72), p = 0.0005], PFS [HR 0.45 (0.24-0.80), p = 0.0059] and CSS [HR 0.31 (0.13-0.67), p = 0.0021].ConclusionHigh mRNA expression of PDL1 predicts improved RFS, PFS and CSS of pT1 NMIBC. Following prospective validation, this objective measurement of PD-L1 might help stratify patients with NMIBC for immunotherapy and identify patients who might benefit from early cystectomy.